Farmers’ and Breeders’ Rights: Bridging Access to, and IP Protection of, Plant Varieties in Africa - Munyi, Peter; De Jonge, Bram (My University, 2015)
Studies in Africa have shown that saving, using, exchanging and selling farm-saved seed is the main channel through which farmers access seed and planting material. Moreover, these saving and related practices are recognised in international law, mainly through the International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty), which many African countries have ratified. These practices are also recognised by, inter alia, obligations at the national level to protect traditional knowledge relevant to seeds and planting material. The standard being employed in developing plant variety protection (PVP) mechanisms in Africa, as with elsewhere in the world, is the 1991 revision of the Convention of the International Union for the Protection of New Varieties of Plants (UPOV, 1991). This Convention has, since its inception, been developed with reference to developed-world farming practices. This article looks at how farmers’ rights are enshrined in Africa’s legal frameworks, and the extent to which the current process of developing regional PVP systems on the continent is taking farmers’ rights into account. The article then makes recommendations on how a balance can be struck between farmers’ and breeders’ rights, while still complying with the UPOV 1991 framework.
Keywords: breeders’ rights; policy review; farmers’ rights; intellectual property; plant varieties; plant variety protection (PVP); smallholder farmers